2008
DOI: 10.1007/s10586-008-0053-z
|View full text |Cite
|
Sign up to set email alerts
|

An autonomic provisioning framework for outsourcing data center based on virtual appliances

Abstract: As outsourcing data centers emerge to host applications and services from many different organizations, it is critical for data center owners to isolate different applications while dynamically and optimally allocate sharable resources among them. To address this issue, we propose a virtual-appliance-based autonomic resource provisioning framework for large virtualized data centers. We present the architecture of the data center with enriched autonomic features. We define a non-linear constrained optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The goal of this feature is to model the delay in adding/removing servers in data centers or the time-to-deploy of virtual machines in Cloud environments [59]. Reconfigurations are implemented as simple modifications of the parallelism degree attribute of the Operating Part.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of this feature is to model the delay in adding/removing servers in data centers or the time-to-deploy of virtual machines in Cloud environments [59]. Reconfigurations are implemented as simple modifications of the parallelism degree attribute of the Operating Part.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The simulator can reproduce a reconfiguration overhead implemented by a variable waiting time before re-starting the execution with a different parallelism degree. The goal of this feature is to model the delay in adding/removing servers in data centers or the time-to-deploy of virtual machines in Cloud environments [59].…”
Section: Adaptive Horizon and Feasibility Of The Approachmentioning
confidence: 99%
“…Sun et al [4] showed that, by utilizing virtual appliances, the deployment process of virtual machines can be made simpler and easier. Wang et al [12] presented a framework to improve the efficiency of resource provisioning in large data centers using virtual appliances. Similarly, a framework for service deployment in cloud based on virtual appliances and virtual machines has been introduced in our previous work [13].…”
Section: Related Workmentioning
confidence: 99%
“…In FCBB, the process of searching for providers begins from a start node (vertex) S v , which has a minimum deployment cost (including appliance and virtual unit cost), and for all its children, there can be found at least one provider that satisfies all constraints (partial forward checking; Algorithm 2, lines [12][13][14]. The partial forward checking on the problem constraints is added to the algorithm to avoid back jumps in the circumstances where latency constraints of the users are comparatively tight.…”
Section: Forward-checking-based Backtrackingmentioning
confidence: 99%
“…To simplify the problem of resource assignments one could use virtualization of hardware resources to dynamically assign extra resources to an application as suggested by [19,20]. However, that approach still requires support from the application for deployment on a cluster, be it virtual or not.…”
Section: Related Workmentioning
confidence: 99%